Metal-loaded starch aerogel as well as preparation method and application thereof

By synthesizing metal-carrying starch aerogels with metal nanoparticles in situ on the starch matrix, the problem that the prior art is difficult to effectively capture fruit endogenous ethylene in low temperature, atmospheric pressure and high humidity environments is solved, and efficient and stable ethylene adsorption and fruit preservation effects are achieved.

CN119549073AActive Publication Date: 2025-03-04SOUTH CHINA UNIV OF TECH +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411623040.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-04
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively capture and remove fruit endogenous ethylene in low temperature, normal pressure and high humidity fruit storage and transportation environments, resulting in poor fruit preservation effect.

Method used

Using metal-carrying starch aerogel, metal nanoparticles are synthesized in situ on the starch matrix, and the π complexation between metal and ethylene and the capillary adsorption effect of starch aerogel are used to achieve efficient adsorption of ethylene.

Benefits of technology

The metal-carrying starch aerogel exhibits excellent ethylene adsorption amount and adsorption stability under normal temperature and pressure conditions. The ethylene semi-release time can reach more than 500 hours, significantly extending the shelf life of the fruit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549073A_ABST
    Figure CN119549073A_ABST
Patent Text Reader

Abstract

The invention discloses metal-loaded starch aerogel as well as a preparation method and application thereof, and the preparation method comprises the following steps: (1) preparing starch milk from starch and water, and heating the starch milk to obtain gelatinized starch liquid; (2) adding sodium laurate into the gelatinized starch liquid, and carrying out heating reaction to obtain a starch-sodium laurate compound solution; (3) adding a metal nitrate solution into the compound solution, uniformly stirring, and adding a reducing agent to reduce metal ions to obtain metal-loaded starch hydrogel; and (4) pre-freezing the hydrogel, and freeze-drying to obtain the metal-loaded starch aerogel. The metal-loaded starch aerogel has excellent ethylene adsorption capacity, the adsorption capacity is about 32 mL / g, and the adsorption stability is good; and the adsorption process can be carried out under normal temperature and normal pressure conditions, and can be used for fruit preservation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the fields of food, materials and chemical industry, and relates to a metal-loaded starch aerogel, and in particular to a starch aerogel loaded with metal nanoparticles and having high-efficiency ethylene adsorption capacity, and a preparation method thereof. Background Art

[0002] my country is rich in fruit resources, but the loss rate during harvesting, storage and transportation is as high as 20-30%, far exceeding that of developed countries such as Europe and the United States (5-6%), which seriously restricts the high-quality development of the fruit industry and the increase of farmers' income. Ethylene is a plant hormone that promotes fruit ripening. It slowly accumulates during the development of the fruit. When it increases to a certain concentration, it will accelerate the ripening and corruption of the fruit. Regulating the concentration of ethylene is an effective way to increase the storage time and quality of fruits.

[0003] At present, ethylene removers and adsorption carriers include potassium permanganate, ozone, activated carbon, zeolite and cyclodextrin. Potassium permanganate oxidants oxidize ethylene into water and carbon dioxide to achieve ethylene removal. Potassium permanganate is attached to a fiber membrane to adsorb the ethylene produced by oxidized avocado, extending the shelf life by 4 days (Journal of Agricultural and Food Chemistry, 2018, 66, 5635-5643). However, such oxidants have defects such as oxidative corrosion, food contamination, and incomplete ethylene removal, resulting in poor fruit preservation. Materials such as cyclodextrin and V-type crystalline starch that rely on van der Waals forces and hydrophobic interactions to achieve ethylene adsorption require high pressure conditions to achieve ethylene adsorption, and there are still huge challenges in capturing extremely low concentrations of ethylene produced by the fruit itself (Aggregate, 2024, e565). Activated carbon and zeolite are also used for ethylene adsorption due to their large specific surface area, but the adsorption amount is low, 3.5-4.1 mL / g and 29.1-439 μL / g, respectively, and the ethylene adsorption is unstable and easy to release (Environmental Research, 2024, 248, 118247; Comprehensive Reviews in Food Science and Food Safety, 2020, 19, 3980-4007). In summary, existing materials such as cyclodextrin and V-type crystalline starch need to use high pressure to push ethylene to contact with binding sites on the surface or pores of the solid matrix; the binding energy of porous materials such as activated carbon and zeolite with ethylene is not strong, and in the actual low temperature and high humidity storage and transportation environment, the ethylene partial pressure produced by fruits and vegetables is low, and the binding adsorption amount achieved by physical force alone is low, easy to desorb, and not suitable for the capture and removal of endogenous ethylene and fruit preservation. Therefore, for the low temperature, normal pressure, and high humidity fruit storage and transportation environment, a stronger binding mode is needed to achieve the adsorption of trace ethylene to slow down the ripening and corruption of fruits.

[0004] As a new type of sustainable aerogel, starch-based aerogel not only has the characteristics of low density and high specific surface area, but also has new properties when mixed with other materials to form a composite material, which is widely used in food packaging and sewage treatment. However, there is no research in China on the removal of ethylene during fruit preservation using metal-loaded starch aerogel. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a metal-loaded starch aerogel which is convenient to use, low in cost and environmentally friendly, so as to achieve efficient ethylene adsorption and fruit preservation functions.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a metal-loaded starch aerogel comprises the following steps:

[0008] (1) preparing starch milk with starch and water, and heating the starch milk to obtain gelatinized starch liquid;

[0009] (2) adding sodium laurate to the gelatinized starch solution to carry out a heating reaction, and obtaining a starch-sodium laurate complex solution after the reaction is completed;

[0010] (3) adding a metal nitrate solution to the above-mentioned complex solution, stirring evenly, and then adding a reducing agent to reduce the metal ions to obtain a metal-loaded starch hydrogel;

[0011] (4) Prefreezing the hydrogel and then freeze-drying it to obtain the metal-loaded starch aerogel.

[0012] Preferably, in step (3), the reducing agent is sodium borohydride and / or glucose, and the molar ratio of the reducing agent to the metal nitrate is 1:2 to 2:1.

[0013] Preferably, in step (3), the metal nitrate is copper nitrate and / or silver nitrate, and the amount used is 1-5% of the dry weight of starch.

[0014] Preferably, in step (2), the mass of the sodium laurate is 8-20% of the dry basis of starch.

[0015] Preferably, the sodium laurate is added in the form of a solution, and the sodium laurate solution needs to be preheated at 80 to 90° C. for 5 to 10 minutes.

[0016] Preferably, the heating reaction is carried out at a temperature of 80 to 120° C. and with continuous stirring for 0.5 to 2 h.

[0017] Preferably, the molar ratio of the reducing agent to the metal nitrate is 1:1; the mass of the sodium laurate is 10-15% of the dry basis of starch; and the conditions of the heating reaction are a heating temperature of 95±5° C. and continuous stirring for 1.2±0.2 h.

[0018] Preferably, in step (1), the starch is one of potato starch, corn starch, cassava starch and wheat starch; and the concentration of the starch milk prepared by the starch is 5 to 10% w / w.

[0019] Preferably, in step (1), the starch milk is heated at 100-120° C. for 1-2 h and kept stirring; the stirring conditions in step (3) are a speed of 500-2000 rpm for 5-20 min; and after reduction, it is also subjected to high-speed shearing at a shearing speed of 8000-10000 rpm for 2-5 min.

[0020] Preferably, in step 3), the reducing agent is added dropwise under stirring at a rate of 20 to 40 mL / h; in step 4), the pre-freezing conditions are: soaking in liquid nitrogen for 10 to 20 min; the freeze-drying conditions are: temperature of -60 to -30°C; vacuum degree of 30 to 10 Pa; and drying time of 24 to 72 h.

[0021] The metal-loaded starch aerogel prepared by the above method is used in fruit preservation (such as packaging materials, etc.) and the adsorption of ethylene, oxygen and carbon dioxide.

[0022] The metal-loaded starch aerogel provided by the present invention is prepared by in-situ synthesis of metal nanoparticles on a starch gel matrix, and is prepared by freeze-drying through deposition of metal ions on the starch matrix and in-situ reduction. The special π-complexation between metal and ethylene is utilized to achieve stable capture of ethylene, and the capillary adsorption effect of the starch aerogel gives it ethylene adsorption characteristics and fruit preservation ability.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The metal-loaded starch aerogel prepared by the present invention has good ethylene adsorption capacity and adsorption stability. For example, the ethylene adsorption capacity of silver-loaded starch aerogel and copper-loaded starch aerogel under normal temperature and pressure conditions is 25.31-30.49 mL / g and 26.93-32.51 mL / g; after being placed for 80 hours, the release rates are only 14-16% and 15-21%, respectively. The metal-loaded starch aerogel exhibits excellent fruit preservation effect and can extend the shelf life of bananas by more than 7 days.

[0025] (2) The present invention prepares metal-loaded starch aerogels through in-situ reduction to obtain aerogels with high specific area, low density and strong ethylene adsorption capacity, which can be used for ethylene control in the process of fruit preservation. Compared with adsorption matrices such as zeolite and activated carbon, the ethylene adsorption capacity is more prominent, and the ethylene half-release time is greatly improved to more than 500 hours, and the maximum can reach 1580.86 hours, and the adsorption process can be carried out under normal temperature and pressure conditions; in addition, the block material has more advantages than the powder product in the application process.

[0026] (3) The present invention achieves reversible adsorption of ethylene gas through metal-gas interaction. Compared with potassium permanganate-based ethylene oxidation removal agents, no by-products such as water and carbon dioxide are produced during the adsorption process, which does not affect the respiratory environment of fruits. In addition, ethylene can be desorbed and reused by simple heating.

[0027] (4) The present invention achieves fruit preservation by gas adsorption. Compared with the use of 1-methylcyclopropene ethylene inhibitors, the metal-loaded aerogel of the present invention does not have the problems of uneven and irreversible ripening of fruits, thereby greatly reducing the cost of fruit preservation.

[0028] (5) The present invention utilizes cheap starch materials to reduce economic costs and achieve environmentally friendly, green, and sustainable ethylene adsorption functions. The preparation process is simple and the conditions are mild, which is suitable for laboratory operations and can be realized in industrial production, greatly expanding the application scope of starch-based adsorption materials and having good social and economic value for the promotion and use of the metal-loaded starch aerogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the silver-loaded starch aerogel prepared in Example 1 of the present invention.

[0030] Figure 2 This is a curve showing the hardness change of bananas when the silver-loaded starch aerogel prepared in Example 1 of the present invention is used in a banana preservation test.

[0031] Figure 3 This is the change curve of soluble solid content of bananas when the silver-loaded starch aerogel prepared in Example 1 of the present invention is used in a banana preservation test. DETAILED DESCRIPTION

[0032] The present invention is described below by means of specific embodiments, but the scope of protection claimed in the present invention is not limited thereto.

[0033] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the raw materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified. Ordinary corn starch was purchased from Changchun Dacheng Industrial Group Co., Ltd., and wheat starch was purchased from Henan Feitian Biotechnology Co., Ltd.

[0034] Determination of Ethylene Adsorption of Metal-loaded Starch Aerogels

[0035] In the embodiment, the ethylene adsorption amount of the metal-loaded starch aerogel is obtained by headspace gas chromatography. Specifically, the sample is degassed at 85°C for 10 hours and then placed in a 20 mL gas phase bottle, and 2 mL of high-purity ethylene is injected into the bottle. After 24 hours of adsorption under normal pressure, 1 mL of headspace gas is extracted using a syringe and analyzed using a gas chromatograph (GC) (Agilent 7890A, Agilent Technologies, Palo Alto, CA, USA) equipped with a DANI HS 86.50 automatic headspace sampler (DANI Instruments SpA, Cologno Monzese, Italy). The ethylene concentration is determined with reference to the calibration curve and is recorded as V0. Under the same conditions, the ethylene concentration is measured using a control group without a sample, which is recorded as V1. The ethylene adsorption capacity (C) of the sample is calculated by formula (1):

[0036]

[0037] Where m is the sample mass.

[0038] Determination of ethylene half-release time of metal-loaded starch aerogels

[0039] In the embodiment, the ethylene half-release time of the metal-loaded starch aerogel is calculated by release kinetics. Specifically, the sample after ethylene adsorption is transferred to a 50 mL test tube, and 1 mL of gas is periodically extracted at 25°C to determine the ethylene concentration. The release kinetics is modeled using the Avrami equation (2):

[0040]

[0041] Wherein, X represents the ethylene release at time t (h), k is the release rate constant, and n is the Avrami parameter. The calculation formula (3) of ethylene half-release time (X = 0.5) is as follows:

[0042]

[0043] Determination of fruit maturity index in preservation experiment

[0044] In the embodiment, the preservation ability of the material on the fruit is determined by characterizing the soluble solid content and hardness of the fruit, wherein the fruit is selected as banana. Specifically, fresh bananas are selected to be kept fresh in a 2.5L sealed container at a relative humidity of 75.5% and an ambient temperature of 75.5%, and the amount of the material is 0.2g. A small amount of juice is extracted from each banana and analyzed using a portable refractometer (RHB32) at 25°C to determine the soluble solid content. The hardness of the banana is evaluated using a handheld hardness meter (GY-5A).

[0045] Comparative Example 1

[0046] (1) Preparation of starch-sodium laurate complex solution

[0047] 5 g of ordinary corn starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was stirred and heated at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was stirred and heated at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0048] (2) Preparation of starch hydrogel

[0049] The obtained starch-sodium laurate complex solution was cooled to room temperature, and then 0.5 g of gluconolactone (10% of the dry weight of starch) was added, and the solution was allowed to stand overnight to obtain a starch hydrogel.

[0050] (3) Preparation of starch aerogel

[0051] The starch hydrogel was immersed in liquid nitrogen for 5 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0052] It was determined that the ethylene adsorption capacity of the obtained starch aerogel was 15.0 mL / g; the ethylene half-release time of the obtained starch aerogel was 36.27 h.

[0053] Example 1

[0054] (1) Preparation of starch-sodium laurate complex solution

[0055] 5 g of ordinary corn starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was stirred and heated at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was stirred and heated at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0056] (2) Silver ion loading and reduction

[0057] 2 mL of silver nitrate solution (0.4 mol / L) was added to the starch-sodium laurate complex solution at 50°C, and the stirring speed was maintained at 1000 rpm. After 10 minutes, 8 mL of sodium borohydride solution (0.1 mol / L) was added to reduce the silver ions in situ to silver nanoparticles.

[0058] (3) Preparation of silver-loaded starch hydrogel

[0059] The above solution was placed under a high-speed shearing machine at a shearing speed of 10000 rpm and a shearing time of 5 min, and then allowed to stand to obtain a silver-loaded starch hydrogel.

[0060] (4) Preparation of silver-loaded starch aerogel

[0061] The obtained hydrogel was immersed in liquid nitrogen for 10 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0062] It was determined that the ethylene adsorption capacity of the obtained silver-loaded starch aerogel was 30.5 mL / g; the ethylene half-release time of the obtained silver-loaded starch aerogel was 1580.86 h.

[0063] Example 2

[0064] (1) Preparation of starch-sodium laurate complex solution

[0065] 5 g of ordinary corn starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was stirred and heated at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was stirred and heated at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0066] (2) Silver ion loading and reduction

[0067] 2 mL of silver nitrate solution (0.4 mol / L) was added to the starch-sodium laurate complex solution at 50°C, and the stirring speed was maintained at 1000 rpm. After 10 minutes, 8 mL of glucose solution (0.1 mol / L) was added to reduce the silver ions in situ to silver cluster particles.

[0068] (3) Preparation of silver-loaded starch hydrogel

[0069] The above solution was placed under a high-speed shearing machine at a shearing speed of 10000 rpm and a shearing time of 5 min, and then allowed to stand to obtain a silver-loaded starch hydrogel.

[0070] (4) Preparation of silver-loaded starch aerogel

[0071] The obtained hydrogel was immersed in liquid nitrogen for 10 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0072] It was determined that the ethylene adsorption capacity of the obtained silver-loaded starch aerogel was 25.3 mL / g; and the ethylene half-release time of the obtained silver-loaded starch aerogel was 974.87 h.

[0073] Example 3

[0074] (1) Preparation of starch-sodium laurate complex solution

[0075] 5 g of ordinary corn starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was stirred and heated at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was stirred and heated at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0076] (2) Loading and reduction of copper ions

[0077] 2 mL of copper nitrate solution (0.4 mol / L) was added to the starch-sodium laurate complex solution at 50°C, and the stirring speed was maintained at 1000 rpm. After 10 minutes, 8 mL of sodium borohydride solution (0.1 mol / L) was added to reduce the copper ions in situ to copper nanoparticles.

[0078] (3) Preparation of copper-loaded starch hydrogel

[0079] The solution was placed under a high-speed shearing machine at a shearing speed of 10000 rpm and a shearing time of 5 min, and then allowed to stand to obtain a copper-loaded starch hydrogel.

[0080] (4) Preparation of copper-loaded starch aerogel

[0081] The obtained hydrogel was immersed in liquid nitrogen for 10 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0082] It was determined that the ethylene adsorption capacity of the obtained copper-loaded starch aerogel was 32.5 mL / g; the ethylene half-release time of the obtained copper-loaded starch aerogel was 574.96 h.

[0083] Example 4

[0084] (1) Preparation of starch-sodium laurate complex solution

[0085] 5 g of ordinary corn starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was stirred and heated at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was stirred and heated at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0086] (2) Loading and reduction of copper ions

[0087] 2 mL of copper nitrate solution (0.4 mol / L) was added to the starch-sodium laurate complex solution at 50°C, and the stirring speed was maintained at 1000 rpm. After 10 minutes, 8 mL of glucose solution (0.1 mol / L) was added to reduce the copper ions in situ to copper cluster particles.

[0088] (3) Preparation of copper-loaded starch hydrogel

[0089] The solution was placed under a high-speed shearing machine at a shearing speed of 10000 rpm and a shearing time of 5 min, and then allowed to stand to obtain a copper-loaded starch hydrogel.

[0090] (4) Preparation of copper-loaded starch aerogel

[0091] The obtained hydrogel was immersed in liquid nitrogen for 10 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0092] It was determined that the ethylene adsorption capacity of the obtained copper-loaded starch aerogel was 26.9 mL / g; the ethylene half-release time of the obtained copper-loaded starch aerogel was 1157.38 h.

[0093] Example 5

[0094] (1) Preparation of starch-sodium laurate complex solution

[0095] 5 g of ordinary corn starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was stirred and heated at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was stirred and heated at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0096] (2) Silver ion loading and reduction

[0097] 2 mL of silver nitrate solution (0.4 mol / L) was added to the starch-sodium laurate complex solution at 50°C, and the stirring speed was maintained at 1000 rpm. After 10 minutes, 4 mL of sodium borohydride solution (0.1 mol / L) was added to reduce the silver ions in situ to silver nanoparticles.

[0098] (3) Preparation of silver-loaded starch hydrogel

[0099] The above solution was placed under a high-speed shearing machine at a shearing speed of 10000 rpm and a shearing time of 5 min, and then allowed to stand to obtain a silver-loaded starch hydrogel.

[0100] (4) Preparation of silver-loaded starch aerogel

[0101] The obtained hydrogel was immersed in liquid nitrogen for 10 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0102] It was determined that the ethylene adsorption capacity of the obtained silver-loaded starch aerogel was 28.2 mL / g; the ethylene half-release time of the obtained silver-loaded starch aerogel was 1273.47 h.

[0103] Example 6

[0104] (1) Preparation of starch-sodium laurate complex solution

[0105] 5 g of ordinary corn starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was stirred and heated at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was stirred and heated at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0106] (2) Silver ion loading and reduction

[0107] 2 mL of silver nitrate solution (0.4 mol / L) was added to the starch-sodium laurate complex solution at 50°C, and the stirring speed was maintained at 1000 rpm. After 10 minutes, 4 mL of glucose solution (0.1 mol / L) was added to reduce the silver ions in situ to silver cluster particles.

[0108] (3) Preparation of silver-loaded starch hydrogel

[0109] The above solution was placed under a high-speed shearing machine at a shearing speed of 10000 rpm and a shearing time of 5 min, and then allowed to stand to obtain a silver-loaded starch hydrogel.

[0110] (4) Preparation of silver-loaded starch aerogel

[0111] The obtained hydrogel was immersed in liquid nitrogen for 10 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0112] It was determined that the ethylene adsorption capacity of the obtained silver-loaded starch aerogel was 21.8 mL / g; the ethylene half-release time of the obtained silver-loaded starch aerogel was 692.13 h.

[0113] Example 7

[0114] (1) Preparation of starch-sodium laurate complex solution

[0115] 5 g of ordinary corn starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was stirred and heated at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was stirred and heated at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0116] (2) Loading and reduction of copper ions

[0117] 2 mL of copper nitrate solution (0.4 mol / L) was added to the starch-sodium laurate complex solution at 50°C, and the stirring speed was maintained at 1000 rpm. After 10 minutes, 4 mL of sodium borohydride solution (0.1 mol / L) was added to reduce the copper ions in situ to copper nanoparticles.

[0118] (3) Preparation of copper-loaded starch hydrogel

[0119] The solution was placed under a high-speed shearing machine at a shearing speed of 10000 rpm and a shearing time of 5 min, and then allowed to stand to obtain a copper-loaded starch hydrogel.

[0120] (4) Preparation of copper-loaded starch aerogel

[0121] The obtained hydrogel was immersed in liquid nitrogen for 10 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0122] It was determined that the ethylene adsorption capacity of the obtained copper-loaded starch aerogel was 29.7 mL / g; the ethylene half-release time of the obtained copper-loaded starch aerogel was 864.58 h.

[0123] Example 8

[0124] (1) Preparation of starch-sodium laurate complex solution

[0125] 5 g of wheat starch was dispersed in 95 g of deionized water to prepare a 5% (w / w) starch suspension, which was heated and stirred at 100° C. for 1 h. Subsequently, 0.5 g of sodium laurate (10% of the dry weight of starch) was added, and the mixture was heated and stirred at 90° C. for 1 h to obtain a starch-sodium laurate complex solution.

[0126] (2) Silver ion loading and reduction

[0127] 2 mL of silver nitrate solution (0.4 mol / L) was added to the starch-sodium laurate complex solution at 50°C, and the stirring speed was maintained at 1000 rpm. After 10 minutes, 8 mL of sodium borohydride solution (0.1 mol / L) was added to reduce the silver ions in situ to silver nanoparticles.

[0128] (3) Preparation of silver-loaded starch hydrogel

[0129] The above solution was placed under a high-speed shearing machine at a shearing speed of 10000 rpm and a shearing time of 5 min, and then allowed to stand to obtain a silver-loaded starch hydrogel.

[0130] (4) Preparation of silver-loaded starch aerogel

[0131] The obtained hydrogel was immersed in liquid nitrogen for 10 minutes and then freeze-dried to obtain aerogel. The freeze-drying conditions were: temperature -40°C, vacuum degree 20Pa, and time 48h.

[0132] It was determined that the ethylene adsorption capacity of the obtained silver-loaded starch aerogel was 28.3 mL / g; the ethylene half-release time of the obtained silver-loaded starch aerogel was 1357.3 h.

[0133] Comparative analysis of the ethylene adsorption capacity of the metal-loaded starch aerogels prepared in Example 1 and Examples 1-8:

[0134] Table 1 Ethylene adsorption capacity of metal-loaded starch aerogels

[0135]

[0136]

[0137] As shown in Table 1, the ethylene adsorption of metal-loaded starch aerogel is related to the type of metal, the type of reducing agent and the ratio. The ethylene adsorption of the obtained metal-loaded starch aerogel is much higher than that of starch aerogel, and the ethylene adsorption of the metal-loaded starch aerogel using sodium borohydride as a reducing agent is higher. This is because in addition to the capillary effect provided by the porous structure, the metal in the metal-loaded starch aerogel acts as an active site for ethylene adsorption, which binds ethylene through π complexation, thereby increasing the ethylene adsorption; in addition, sodium borohydride, as a strong reducing agent, has a faster reduction rate than glucose, and the resulting metal particles are smaller in size, which reduces the agglomeration effect of the metal and improves the utilization rate of the metal sites, thereby having a higher ethylene adsorption capacity.

[0138] Depend on Figure 1It can be seen that the microscopic morphology of the starch aerogel loaded with silver nanoparticles presents a three-dimensional mesh open-pore structure. These open-pore structures give the metal-loaded starch aerogel the characteristics of high specific area and uniform dispersion of metal particles. The adsorption capacity of ethylene by the obtained metal-loaded starch aerogel at normal pressure is 21.8-32.5 mL / g, and the half-release time of ethylene is 574.96-1580.86 h, which far exceeds the ethylene adsorption capacity of starch aerogel.

[0139] Analysis of banana preservation ability of metal-loaded starch aerogel prepared in Example 1:

[0140] The starch aerogel loaded with metallic silver has excellent ethylene adsorption capacity and can absorb trace amounts of endogenous ethylene released during the ripening process of bananas, thereby achieving the preservation of bananas. This is because ethylene, as a plant hormone, can initiate the ripening process of fruits. When the endogenous ethylene released by the banana itself into the storage environment is adsorbed by the metal-loaded starch aerogel, the ethylene receptors on the banana cannot be stimulated to respond, and starch, pectin, and cellulose cannot be degraded by enzymes, thus maintaining the freshness of the banana. An appropriate amount of metal-loaded starch aerogel is placed in the banana storage environment, and the degree of maturity is characterized by measuring the hardness and soluble solids content of the banana during the preservation process. Figure 2 It can be seen that after 16 days of storage, the bananas without any treatment and without the use of starch aerogel began to ripen from the 7th day, while the bananas using silver-loaded starch aerogel had only slight changes in hardness and soluble solids content within 16 days, indicating that starch aerogel loaded with metallic silver has a good effect in fruit preservation applications.

[0141] The invention provides a method for preparing a metal-loaded starch aerogel for ethylene adsorption and an application thereof, which can realize efficient adsorption of endogenous ethylene in fruits and has good adsorption stability; the method has low cost and simple preparation process, and is suitable for laboratory operation and can be easily realized in industrial production.

[0142] It should be noted that, for ordinary technicians in the technical field to which the present invention belongs, the implementation mode of the present invention is not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing metal-loaded starch aerogel, characterized in that: The steps include: (1) preparing starch milk with starch and water, and heating the starch milk to obtain gelatinized starch liquid; (2) adding sodium laurate to the gelatinized starch solution to carry out a heating reaction, and obtaining a starch-sodium laurate complex solution after the reaction is completed; (3) adding a metal nitrate solution to the above-mentioned complex solution, stirring evenly, and then adding a reducing agent to reduce the metal ions to obtain a metal-loaded starch hydrogel; (4) Prefreezing the hydrogel and then freeze-drying it to obtain the metal-loaded starch aerogel.

2. The preparation method according to claim 1, characterized in that: In step (3), the reducing agent is sodium borohydride and / or glucose, and the molar ratio of the reducing agent to the metal nitrate is 1:2 to 2:

1.

3. The preparation method according to claim 2, characterized in that: In step (3), the metal nitrate is copper nitrate and / or silver nitrate, and the amount used is 1-5% of the dry weight of starch.

4. The preparation method according to claim 3, characterized in that: In step (2), the mass of the sodium laurate is 8-20% of the dry basis of starch; the heating reaction is carried out at a heating temperature of 80-120° C. and continuous stirring for 0.5-2 h.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the reducing agent to the metal nitrate is 1:1; the mass of the sodium laurate is 10-15% of the dry basis of starch; the conditions of the heating reaction are a heating temperature of 95±5° C. and continuous stirring for 1.2±0.2 h.

6. The method according to any one of claims 1 to 5, characterized in that: In step (1), the starch is one of potato starch, corn starch, cassava starch and wheat starch; the concentration of the starch milk prepared by the starch is 5-10% w / w.

7. The method according to any one of claims 1 to 5, characterized in that: In step (1), the starch milk is heated at 100-120° C. for 1-2 h and kept stirred; in step (3), the stirring conditions are a speed of 500-2000 rpm and a time of 5-20 min; After reduction, it is further subjected to high-speed shearing, with a shearing speed of 8000-10000 rpm and a time of 2-5 minutes.

8. The method according to any one of claims 1 to 5, characterized in that: In step 3), the reducing agent is added dropwise under stirring at a rate of 20 to 40 mL / h; in step 4), the pre-freezing conditions are: soaking in liquid nitrogen for 10 to 20 min; the freeze-drying conditions are: temperature of -60 to -30°C; vacuum degree of 30 to 10 Pa; and drying time of 24 to 72 h.

9. The metal-loaded starch aerogel prepared by the method according to any one of claims 1 to 8.

10. Use of the metal-loaded starch aerogel according to claim 9 in fruit preservation and ethylene, oxygen and carbon dioxide gas adsorption.

Citation Information

Patent Citations

  • Application of polyvinyl alcohol composite hydrogel in Raman spectrum for detecting rhodamine

    CN107525795A

  • Preparation method of graphene-based hydrogel loaded with silver nanoparticles

    CN109569450A

  • High-dispersion metal or metal oxide doped adsorbent as well as preparation method and application thereof

    CN112844317A

  • Starch-based aerogel as well as preparation method and application thereof

    CN115232356A

  • In-situ silver modified pure silicon molecular sieve and application thereof in capturing low-concentration ethylene under humid condition

    CN115646436A